Determining the optimized interlayer separation distance in vertical stacked 2D WS2 :hBN:MoS2 heterostructures for exciton energy transfer - Xu, W; Kozawa, D; Liu, Y; Sheng, Y; Wei, K; Koman, VB; Wang, S; Wang, X; Jiang, T; Strano, MS; Warner, JH (Wiley, 2018)
The 2D semiconductor monolayer transition metal dichalcogenides, WS2 and MoS2 , are grown by chemical vapor deposition (CVD) and assembled by sequential transfer into vertical layered heterostructures (VLHs). Insulating hBN, also produced by CVD, is utilized to control the separation between WS2 and MoS2 by adjusting the layer number, leading to fine-scale tuning of the interlayer interactions within the VLHs. The interlayer interactions are studied by photoluminescence (PL) spectroscopy and are demonstrated to be highly sensitive to the input excitation power. For thin hBN separators (one to two layers), the total PL emission switches from quenching to enhancement by increasing the laser power. Femtosecond broadband transient absorption measurements demonstrate that the increase in PL quantum yield results from Förster energy transfer from MoS2 to WS2 . The PL signal is further enhanced at cryogenic temperatures due to the suppressed nonradiative decay channels. It is shown that (4 ± 1) layers of hBN are optimum for obtaining PL enhancement in the VLHs. Increasing thickness beyond this causes the enhancement factor to diminish, with the WS2 and MoS2 then behaving as isolated noninteracting monolayers. These results indicate how controlling the exciton generation rate influences energy transfer and plays an important role in the properties of VLHs.